Energy gap tunable graphene antidot nanoribbon MOSFET: A uniform multiscale analysis from band structure to transport properties. (May 2016) - Lv, Yawei; Chang, Sheng; Wang, Hao; He, Jin; Huang, Qijun
Abstract: A detailed simulation study of the graphene antidot nanoribbon (GANR) and its corresponding MOSFET characteristics is shown in this paper. The research uncovers that the GANR's energy gap ( E g ) is continuously tunable by its topography parameters, such as the ribbon's width, the antidot density and the antidot size. At the same ribbon width, the E g of GANR can be tuned flexibly, while it is only a fixed value in GNR. Owing to these flexible E g regulations, device applications based on GANRs could be more widely used. Furthermore, brief compact descriptions are extracted between GANR's band gap and MOSFET's device characteristics. Using E g as a bridge, the relations between the structure characteristics and transport properties of GANR MOSFETs are constructed directly. The results reveal that the antidot nanoribbon structure is a good candidate for MOSFET applications. In the calculation, an elaborate ab initio-based study framework from band structure to device performance is adopted. Using the maximally localized Wannier functions (MLWF) method, the impacts on band structures, which are induced by crystal optimizations, are reserved into the TB Hamiltonian without any parameter revisions. This method overcomes the gap between nano-scale carbon structures' material characteristics and their device applications.